Legal Analysis of Judges on Strike for Salary Increase: Ethical Violation or Constitutional Rights? - Muhammad Arafat; Alexander Tito Enggar Wirasto (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study highlights the conflict between judges’ constitutional right to strike and their professional ethical code demanding integrity and neutrality in judicial duties. Using a normative approach through regulatory review, case analysis, and international policy comparison, this research finds that while the right to strike is acknowledged in Article 28E of the 1945 Constitution, its application to judges presents significant challenges. Judges, as enforcers of justice, have a responsibility to uphold the profession’s dignity, and engaging in strikes for salary demands risks eroding credibility and public trust. The findings show that strikes by judges in Indonesia often breach ethics as stipulated in the Code of Ethics and Guidelines for Judges’ Conduct (KEPPH), where such actions are viewed as prioritizing personal interests over judicial duties. Comparative studies indicate that judges’ involvement in similar actions may harm public perception and disrupt institutional stability. As a solution, this study recommends stricter regulations on judges’ work rights and limitations, along with comprehensive welfare policies to meet judges’ economic needs without compromising professional ethics. With clear regulations, a balance can be achieved between judges’ constitutional rights and the obligation to maintain judicial integrity and public trust.